(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
This article gives an overview of India’s ’para’ instructors. It recounts the beginnings of para-teacher programs in the nation and examines the shifting policy environment in which contract para teachers with little pay and training are increasingly being hired in lieu of regular teachers. Teachers at public schools. Incorporating existing research. The authors of the research call attention to the negative consequences that the purpose of para teacher programs is to help teachers become more professional. Concerns about educational quality and equality. Another significant development in the past decade is Parliament’s adoption of a Constitutional Amendment making education for children aged 6 to 14 years a basic right of all citizens. . Meanwhile, via the National Literacy Mission, efforts to improve literacy were galvanized with mass literacy campaigns across the length and width of the nation. Another significant development in the past decade is Parliament’s adoption of a Constitutional Amendment making education for children aged 6 to 14 years a basic right of all citizens. The process of drafting central legislation to make the constitutional clause effective is now ongoing